ASSOCIATION OF E-CADHERIN EXPRESSION TO CLINICAL STAGE OF NASOPHARYNGEAL CARCINOMA - Felicia Melani Triastuti; Rizalina A. Asnir; Ashri Yudhistira; Sutoyo Eliandy (INTERNATIONAL JOURNAL OF NASOPHARYNGEAL CARCINOMA, 2019)
Background: Nasopharyngeal carcinoma (NPC) has a high incidence rate in southern China and Southeast Asia and a high rate of metastasis in head and neck cancer. NPC is a squamous cell carcinoma that grows from the surface of the lateral wall of the nasopharynx. E-cadherin is known as a tumor suppressor protein and the loss of this expression in tumor cells is related to epithelial-mesenchymal transition that occurs during tumor development and metastasis. Objective:To determine the relationship between E-cadherin expression and clinical stage in patients with nasopharyngeal carcinoma. Methods: An analytical study with a cross-sectional study design, the number of samples was 30 patients with NPC who underwent immunohistochemical examination on KNF paraffin block. Result: Overexpression of E-cadherin was found in T1 and T2 of 15 subjects (100%). The overexpression of E-cadherin was found in lymph node N2 and N3 of 19 subjects (95%). The overexpression of E-cadherin was found in the histopathological type of Non-Keratinizing Squamous Cell Carcinoma of 24 subjects (96%). The overexpression of E-cadherin was found at an advanced stage of 26 subjects (100%). Conclusion: No significant association was found between E-cadherin expression and tumor size (p = 1,000), lymph node metastasis (p = 1,000), histopathological type (p = 1,000) and tumor stage (p = 0.133).